Localized visualization, analysis and quantification of pulmonary parenchyma deformations in 3D images in presence of acute respiratory distress syndrome (ARDS) (2016)
"Acute Respiratory Distress Syndrome (ARDS) is a life threatening respiratory condition characterized by hypoxemia (Iow oxygen), change in tissue homogeneity, inflammation and increased permeability in the lung. ARDS is a very heterogeneous pathology both in causes and anatomy. In most cases mechanical ventilation is needed to keep patients alive while the cause is treated. The objective of the work presented in this report is to obtain and display data found from lung CT scans to assess ventilation parameter settings and reduce collateral damage produced by an unfitting ventilation. A general method for lung aeration quantification is proposed along with a measure for tissue inhomogeneity and tissue expansion. The general quantification method allows for a global, regional or local measure. This method is used in the context of the project to calculate local recruitment, i.e, opening of collapsed alveoli, enabling to locate and measure the impact of successfully reopened regions..."